Studies on the Preservation of Buck Seman - Balakrishnan P P (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 1979)
With the ultimate object of evolving a suitable extender for buck semen, 64 ejaculates from eight healthy cross bred bucks (6 saanen x Malabari and 2 Alpine x Malabari) selected at random from “ All India Co-ordinated Research Project on Goats for Milk Production”, Mannuthy, were used for the preservation studies. Six diluents viz., Tris, Skim milk citrate fructose glycine (SMCFG), milk citrate fructose glycine (MCFG), whole cows milk (CM), whole goats milk (GM) and Cornell University Extender (CUE) were stored at 50C and at room temperature in coconut milk extender (CME). Buck semen could be stored up to 60 hours in Tris, SMCFG and MCFG with good motility at 50C. In CME, semen could be stored only up to 24 hours in 1: 200 dilution. Egg yolk containing diluents proved to be least suitable for preservation of buck semen at 50 C. The percentage of conception rate was 44.0, 52.0 and 53.3 with Tris, SMCFG and MCFG diluents respectively.